2004
DOI: 10.1074/jbc.m401770200
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E Receptors Are Required for Reelin-induced Proteasomal Degradation of the Neuronal Adaptor Protein Disabled-1

Abstract: Dab1 consists of an aminoterminal phosphotyrosine binding domain followed by a stretch of tyrosyl residues and a large carboxyl-terminal domain. At least two of the tyrosine residues are phosphorylated in vivo by the Src family kinase Fyn (2, 3) in response to Reelin. Tyrosine phosphorylation of Dab1 at these residues is essential for the transduction of the Reelin signal (4) and requires binding of Reelin to its receptors, apolipoprotein E receptor 2 (apoER2) and VLDL receptor, two members of the low density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(103 citation statements)
references
References 62 publications
3
100
0
Order By: Relevance
“…This hypothesis is supported by studies in transgenic animals showing ectopic accumulations of Dab1 in Reelin-, ApoER2-, and VLDLR-deficient mice (Rice and Curran, 2001;Trommsdorff et al, 1999). In-vitro studies showed that internalization of Reelin-ApoER2 complexes is required for endocytosis and proteasomal degradation of Dab1 (Bock et al, 2004;D'Arcangelo et al, 1999). A direct role of Reelin in APP processing is demonstrated by the increased co-immunoprecipitation of Dab1 with ApoER2 and APP and decreased Aβ production (Hoe et al, 2006a), indicating that reduced Reelin levels might favor the production of neurotoxic Aβ species.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…This hypothesis is supported by studies in transgenic animals showing ectopic accumulations of Dab1 in Reelin-, ApoER2-, and VLDLR-deficient mice (Rice and Curran, 2001;Trommsdorff et al, 1999). In-vitro studies showed that internalization of Reelin-ApoER2 complexes is required for endocytosis and proteasomal degradation of Dab1 (Bock et al, 2004;D'Arcangelo et al, 1999). A direct role of Reelin in APP processing is demonstrated by the increased co-immunoprecipitation of Dab1 with ApoER2 and APP and decreased Aβ production (Hoe et al, 2006a), indicating that reduced Reelin levels might favor the production of neurotoxic Aβ species.…”
Section: Discussionmentioning
confidence: 80%
“…Transduction of the signal involves the interaction of the adapter protein Dab1 with the intracellular NPxY motiv of these receptors, resulting in tyrosine phosphorylation of Dab1, activation of Src family of non-receptor tyrosine kinases, and triggering a downstream cytosolic kinase cascade beginning with the activation of phosphatidylinositol-3-kinase (PI3K) and ending with the inhibition of glycogen synthase kinase 3β (GSK3β; for recent review, see Herz and Cheng, 2006). The signal is terminated with Reelin targeted to the lysosome and Dab1 degraded by the proteasome (Arnaud et al, 2003;Bock et al, 2004;Morimura et al, 2005). In the adult brain, Reelin expression is maintained by GABAergic interneurons and glutamatergic pyramidal neurons in layer II of the entorhinal cortex (Alcantara et al, 1998;Miettinen et al, 2005;Pesold et al, 1998;Ramos-Moreno et al, 2006) and the same signalling cascade is used in adult synapses to modulate neuronal function and synaptic plasticity by regulating glutamate receptor activity through the phosphorylation of intracellular tyrosine residues (Beffert et al, , 2006Chen et al, 2005;Weeber et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…3A). Because neuron cultures contain low levels of Reelin [25], and Dab1 turnover is increased following Reelin-stimulated tyrosine phosphorylation [26,27], increased levels of K45Q and S114T are consistent with decreased Reelin-dependent phosphorylation. Following acute Reelin stimulation, endogenous Dab1 in all cultures and wildtype, S19A and K45Q mutant Dab1-EGFP were tyrosine phosphorylated at increased levels (Fig.…”
Section: Resultsmentioning
confidence: 89%
“…Several recent advances provide further understanding of the mechanism of this posttranscriptional down-regulation of Dab1. Arnaud et al (2003a) and Bock et al (2004) previously showed in primary neuronal cultures that Dab1 is down-regulated through polyubiquitination and targeting to the proteasome in the presence of Reelin, and that this modification requires tyrosine phosphorylation of Dab1. Moreover, inhibition of Dab1 tyrosine phosphorylation and inhibition of SFK activation blocks Dab1 down-regulation (Arnaud et al 2003b;Bock et al 2004;Kuo et al 2005).…”
Section: Down-regulating Dab1mentioning
confidence: 96%
“…Arnaud et al (2003a) and Bock et al (2004) previously showed in primary neuronal cultures that Dab1 is down-regulated through polyubiquitination and targeting to the proteasome in the presence of Reelin, and that this modification requires tyrosine phosphorylation of Dab1. Moreover, inhibition of Dab1 tyrosine phosphorylation and inhibition of SFK activation blocks Dab1 down-regulation (Arnaud et al 2003b;Bock et al 2004;Kuo et al 2005). Feng et al (2007) identified two critical Dab1 tyrosine phosphorylation sites (primary Tyr198, and also Tyr185), both at YQxI sequences, essential for the Dab1 degradation in response to Reelin, in an embryonic cortical neuron culture system.…”
Section: Down-regulating Dab1mentioning
confidence: 96%